Role of local and distant functional connectivity density in the development of minimal hepatic encephalopathy - Qi, Rongfeng (Sci Rep, 2015)
The progression of functional connectivity (FC) patterns from non-hepatic encephalopathy (non-HE) to minimal HE (MHE) is not well known. This resting-state functional magnetic resonance imaging (rs-fMRI) study investigated the evolution of intrinsic FC patterns from non-HE to MHE. A total of 103 cirrhotic patients (MHE, n = 34 and non-HE, n = 69) and 103 healthy controls underwent rs-fMRI scanning. Maps of distant and local FC density (dFCD and lFCD, respectively) were compared among MHE, non-HE, and healthy control groups. Decreased lFCD in anterior cingulate cortex, pre- and postcentral gyri, cuneus, lingual gyrus, and putamen was observed in both MHE and non-HE patients relative to controls. There was no difference in lFCD between MHE and non-HE groups. The latter showed decreased dFCD in inferior parietal lobule, cuneus, and medial frontal cortex relative to controls; however, MHE patients showed decreased dFCD in frontal and parietal cortices as well as increased dFCD in thalamus and caudate head relative to control and non-HE groups. Abnormal FCD values in some regions correlated with MHE patients’ neuropsychological performance. In conclusion, lFCD and dFCD were perturbed in MHE. Impaired dFCD in regions within the cortico-striato-thalamic circuit may be more closely associated with the development of MHE.